Legal Approaches to Combatting Information Warfare in the Age of Social Media and Misinformation in Indonesia - Nasution, Emmi Rahmiwita (The Easta Journal Law and Human Rights, 2025)
The proliferation of social media platforms in Indonesia has intensified the challenges of combating information warfare and disinformation, posing significant risks to public trust, democratic stability, and national security. This study explores legal approaches to addressing these issues, focusing on the strengths, limitations, and enforcement challenges of Indonesia's regulatory framework, particularly the Electronic Information and Transactions Law (UU ITE). Using a qualitative design, data were gathered through in-depth interviews with five key informants, including legal experts, policymakers, digital media analysts, and civil society representatives. The findings reveal that while the UU ITE provides a foundational legal structure, its effectiveness is hindered by ambiguous provisions, resource constraints, and limited collaboration with social media platforms. Recommendations include revising the UU ITE, enhancing capacity building for enforcement agencies, fostering international cooperation, and promoting public digital literacy. These insights contribute to a nuanced understanding of Indonesia's efforts to balance freedom of expression with the need for regulation in the digital era.